The Literature of the Sages : A Re-Visioning - Hayes, Christine (Compendia Rerum Iudaicarum ad Novum Testamentum, 2022)
This volume presents the major works of classical rabbinic Judaism as inter-related aggregates analyzed through three central themes. Part 1, "Intertextuality," investigates the multi-directional relationships among and between rabbinic texts and nonrabbinic Jewish sources. Part 2, "East and West" explores the impact on rabbinic texts of the cultures of the Hellenistic, Roman, and Christian West and the Sasanian East. Part 3, "Halakha and Aggada," interrogates the relationship of law and narrative in rabbinic sources. This bold volume uncovers alliances and ruptures -- textual, cultural, and generic -- obscured by document-based approaches to rabbinic literature.